Environmental pharmacology: an emerging science - Deshkar, Anuradha T.; Gawali, Ujwala P.; Shirure, Prashant A. (International Journal of Basic & Clinical Pharmacology, 2018)
With continuous rapid expansion of the human population there is escalating demand for resources, including human and veterinary pharmaceuticals. This has lead to rapid development of global pharmaceutical industry and with that increase in issues caused by pharmaceutical products. In recent years a great concern has been expressed over the occurrence and persistence of pharmaceutical products in the environment and their potential impact on environment. Owing to this the new branch of science called environmental pharmacology has sprouted. Environmental pharmacology deals with dispersion and impact of pharmaceutical products on environment. Solutions need to be suggested to save this only liveable planet from ill effects of these pharmaceutical products. This has given birth to the science of Ecopharmacovigilance (EPV).